Improving the Student Memorization Quality through the Haflah Selection Tryout Program at Islamic Boarding School - Hakim, Muhammad Fahrizal; Anas, Syaiful; Baker, Bilal Ibn Naim (QUALITY, 2026)
This study analyzes how the Haflah Selection Try Out Program improves the students’ quality of Qur’anic memorization at the Yanbu’ul Qur’an Tahfidz Islamic Boarding School in Kudus. The study focuses on the planning, implementation, and evaluation processes of the program as strategies to enhance memorization quality. A qualitative field study approach was employed to gain an in-depth understanding of the phenomenon. Data were collected through in-depth interviews, participant observation, and documentation involving the pesantren leader, tahfidz coordinator, supervising teachers, and students participating in the program. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that the Haflah Selection Try Out Program is implemented through systematic planning, which includes determining memorization standards, assessment criteria, examination schedules, and examiner assignments. Implementation involves tiered memorization assessments designed to measure memorization mastery, recitation fluency, tajwid accuracy, and students’ readiness to participate in the haflah graduation process. Continuous evaluation is conducted through feedback, remedial guidance, and regular monitoring of memorization progress. This program significantly improves students’ memorization quality by strengthening retention, enhancing recitation accuracy and fluency, increasing discipline and motivation to learn, fostering self-confidence, and reducing errors during examinations. This study contributes to Qur’anic memorization education by demonstrating that a structured tryout program with continuous assessment and systematic coaching can effectively improve the quality of memorization. These findings may serve as a practical reference for tahfidz institutions seeking to develop sustainable and measurable memorization improvement programs.